Penggunaan Aplikasi G Suite For Education Untuk Meningkatkan Hasil Belajar Pada Materi Pendapatan Nasional Siswa Kelas XI IPS MAN 5 Bojonegoro - Wibowo, Said Edy (Balai Diklat Keagamaan Surabaya, 2022)
This Classroom Action Research (CAR) aims to determine the improvement of learning outcomes and strengthening the character of students in class XI IPS MAN 5 Bojonegoro for the 2021/2022 academic year through the G Suite For Education application on national income materials. This classroom action research uses the Kemmis design model based on cycles, consisting of two cycles where each cycle includes planning (plans), action (action), observation (observations), and reflection (reflection). The steps in the next cycle are planning, action, observation, and reflection. Before entering in cycle 1, preliminary actions were carried out in the form of identifying problems in class XI IPS students with the number of students in class 31 children and the instruments in this study were observation, assignments and tests. The results obtained from the study were based on observational data, assignments and tests. Improvements obtained by implementing the G Suite For Education Application can improve learning outcomes and strengthen student character. This is evident in the achievement of learning outcomes, namely in the 1st cycle of 69. While in the 2nd cycle there was a significant increase of 89. The character of responsibility also increased, before the application of the G Suite For Education Application, many students did not do the task, after the program students are enthusiastic in doing the task. This shows that the application of the G Suite For Education application used has proven to be able to improve learning outcomes and strengthen the character of class XI IPS MAN 5 Bojonegoro students for the 2021/2022 academic year. The field results regarding the effectiveness of the G Suite For Education application are feasible and can be used as one of the learning media in further learning.